2011 IEEE Power and Energy Society General Meeting 2011
DOI: 10.1109/pes.2011.6039633
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the long-term benefits of interruptible load scheme for distribution network investment

Abstract: This paper seeks to measure the long-term benefits brought by the interruptible load scheme (ILS) to network utilities and customers. Normally, the ILS is adopted as necessary to reduce system peak demand. By contrast, this paper states that if the scheme is adopted during network contingencies that drive future reinforcement, great benefits might be obtained. It assumes that the long-term benefits incurred from introducing the scheme needs to be investigated and long-term use-of-system pricing is qualified fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…A number of previous studies have attempted to quantify the potential resource in a number of different manners. Difference in Return on Investment (ROI) between DG and Network Investment [5], [16,17] and Capital expenditure by the Distribution Network Operator (DNO) [18][19][20][21][22] are the most commonly calculated variables. However, some studies have identified methods to calculate the length of investment deferral in years [23,24] and allowable additional load growth due to DG [25] or a combination of the above [4,12,26].…”
Section: Motivationmentioning
confidence: 99%
“…A number of previous studies have attempted to quantify the potential resource in a number of different manners. Difference in Return on Investment (ROI) between DG and Network Investment [5], [16,17] and Capital expenditure by the Distribution Network Operator (DNO) [18][19][20][21][22] are the most commonly calculated variables. However, some studies have identified methods to calculate the length of investment deferral in years [23,24] and allowable additional load growth due to DG [25] or a combination of the above [4,12,26].…”
Section: Motivationmentioning
confidence: 99%